Needs Analysis of a Solar System Module with Augmented Reality to Improve Students’ Communication and Problem-Solving - Adi Frengki Wibowo; Ahmad Amin; Yaspin Yolanda (Kasuari: Physics Education Journal (KPEJ), 2026)
This study aims to analyze the need for developing an Augmented Reality (AR)-based digital module on the Solar System to improve students' scientific communication and problem-solving skills. The research method used a qualitative descriptive approach through observation, interviews, questionnaires, and Focus Group Discussions (FGDs) involving 36 seventh-grade students and a physics teacher. The results of the study indicate that physics learning in the classroom is still dominated by lecture methods and 2D media, making it difficult for students to visualize the concepts of rotation, revolution, and astronomical phenomena in depth. Other findings indicate that students' scientific communication and problem-solving skills are still low due to the lack of exploratory activities and scientific discussions. Teachers and students clearly need interactive digital learning media that can display 3D visualizations and support problem-based learning. The integration of AR technology with the Problem-Based Learning (PBL) model is considered highly relevant to provide more immersive, contextual, and collaborative learning. Thus, the results of this needs analysis serve as an important basis for developing an AR-PBL-based digital module on the Solar System that can strengthen students' conceptual understanding, scientific communication skills, and problem-solving abilities according to the demands of 21st-century learning.